Breast care in 2011 and beyond: state of policy, state of science. Issue 6 (June 2011) - Gass, Jennifer; Bell, John; Dizon, Don S
The National Consortium of Breast Centers (NCoBC) is an interdisciplinary group of medical and allied health professionals, advocates and administrators championing the cause of collaborative care as it relates to breast health and breast cancer. The annual meeting was held in Las Vegas (NV, USA) between 13 and 16 March 2011, and because we are not wholly identified as a breast cancer society, our research and programs are varied. To the best of our ability we represent the diversity of our membership on the planning committee and we are proud of the conference that has just taken place. While ours is not a forum for the presentation of new research, it is the forum used to impart important knowledge from the past year to the most diverse group that meets around the topic of breast care. Important highlights from our meeting will be discussed in the following article.